The Association between Waist-Hip Ratio and Body Fat Composition, and Metabolic Syndrome: A Study at RSUP dr. Kariadi - Reza Aditya Afriansyah; Kristophorus Hery Nugroho Hario Seno; Aryu Chandra; Dwi Ngestiningsih (RSUP Dr. Kariadi, 2024)
Background: Metabolic syndrome, which is a collection of symptoms which are usually include of hypertension, hyperglycemia, dyslipidemia, and central obesity, has various fatal complications. Fat composition is known to have a close relationship with complications of metabolic syndrome. However, measurement of fat usually requires expensive tools and methods. Meanwhile, anthropometric indicators such as waist-to-hip ratio (WHR) have links with metabolic syndrome and central obesity. This study examines whether there is a significant relationship between WHR and body fat composition in patients with metabolic syndrome. Objectives: This study examined relationship between WHR and body fat composition as described in fat percentage, fat mass, visceral fat rating, and degree of obesity in patients with metabolic syndrome. Methods: Cross-sectional observational analytic study was conducted on 51 metabolic syndrome patients at Endocrine Polyclinic, RS dr. Kariadi. Respondents filled out informed consent and questionnaires and measured WHR and body fat composition using Tanita scales. Data analysis was performed by univariate test and bivariate test (Pearson test, Spearman test, or Mann-Whitney test). Results: There is a weak significant negative correlation between WHR and body fat percentage (p = 0.023; r = -.0.318). There is no correlation between WHR and fat mass (p=0.312). There is a weak positive significant correlation between WHR and visceral fat rating (p=0.001; r=0.441). And there is no correlation between WHR and the degree of obesity (p=0.785). Conclusion: WHR has a weak significant correlation with body fat percentage and visceral fat rating in NCEP ATP III metabolic syndrome patients.